A novel closed-circuit circulation system about integrated ethanol-methane fermentation process based on the subcritical water pretreatment of corn stover. (10th April 2018) - Wang, Xin; Gao, Lina; Liu, Lian; Wang, Tao; Yin, Huijun; Lü, Xin
Abstract: For the purpose to fully reutilize wastewater originated in second-generation bioethanol production from corn stover, a novel closed-circuit circulation system of integrated ethanol-methane fermentation process was successfully established based on the subcritical water pretreatment, in which the wastewater was fully recycled for 20 batches. It was indicated that the pH of recycling liquid decreased with the increasing of cycle numbers, which led to the constant enhancement of the pretreatment efficiency as approximately 60% hemicellulose and 50% lignin degradation as well as more than 80% cellulose reserved. Meanwhile, the performance of both ethanol (2.76–6.94 g/L) and methane (382.56–2631.24 mL/L) fermentation reached stability and trended to be self-improved during the 20 batches, which indicated that the designed integrated process was stable and applicable. Furthermore, the variety of microbial community and other processes showed intimate correlation with the physiochemical properties of the recycling liquid. It was promising to apply the system in bioenergy industries to fully reutilize of the wastewater in the future. Graphical abstract: Image 1 Highlights: The wastewater was fully reutilized in a closed-circuit circulation system about integrated ethanol-methane fermentation process. The efficiency of subcritical water pretreatment was constantly enhanced during 20 batches cycles. Ethanol and methane fermentation trended be stable or self-improved during the recycling process. Microbial community of sludge and pH of recycling liquid were crucial to maintain and improve the proposed system.